Design, Fabrication and Optimization of Fast Dissolving Solid Oral Formulations of Nabumetone using Solvent Free Technology by 32 Factorial Design - Bhoyar Pravin Khushalrao; Rajendra Singh Bapna; Revathi A. Gupta; Karunakar Shulka (Journal of Coastal Life Medicine, 2023)
The objective of the present study was to formulate and evaluate fast dissolving solid oral formulations of Nabumetone using solvent free technology. Nabumetone, Nonsteroidal anti-inflammatory drug, with t1/2 approx. 19 hrs and absolute oral bioavailability about 80-85%, indicated for relief of signs and symptoms of rheumatoid arthritis and osteoarthritis. In present study, solvent free technique is used in order to improve the dissolution and oral bioavailability of the model drug with poor solubility and high permeability. Solid oral formulations (F1 – F9) were prepared by direct compression technique using solvent free technology with Kyron t 314 and Musa paradisiaca L as a super disintegrants in different ratios and analyse the usefulness of DOE in the development and optimization of a tablet of a model drug employing 32 full factorial statistical design. The drug-polymer compatibility study was carried out to determine the interactions, if any between the drug and the polymers used in the study. The FTIR, XRD and DSC study revealed that, polymers and excipients used were compatible with drug. The prepared tablets were subjected to various evaluation such as hardness (2.80–3.30 kg/cm2), friability (0.34–0.70%), disintegration time (26–38 s), drug content (95.00–99.05%), water absorption ratio (44–56%), wetting time (44–70 s) and in-vitro drug release shown in 5 min (96.40–99.80%). Optimized batch(F5) when subjected to stability at 40± 20C temperature with relative humidity 75±5% for six months, showed no degradation and change in tablet and showed rapid dissolution and effective in achieving patient compliance.